Animal fats valorization to green transportations fuels: From concept to industrially relevant scale validation. (15th April 2022) - Dimitriadis, Athanasios; Chrysikou, Loukia P.; Kokkalis, Athanasios I.; Doufas, Lambros I.; Bezergianni, Stella
Graphical abstract: Highlights: 98 L animal fats were converted to 100 L green transportation fuels. Mild operating hydrogenation conditions have low hydrogen consumption. Green fuels meet most of the market diesel and HVO standards. Green fuels can be blended up to 20% v/v with market diesel. Animal fats storage is feasible up to 4 months prior their conversion. Abstract: The potential of animal fats hydroconversion is experimentally investigated and validated in industrially relevant scale via the production of 100 L of transportation fuels. The experimental testing has indicated that mild hydrotreatment conditions are associated with low hydrogen consumption without significantly penalties in product quality. The optimal operating conditions (pressure of 6.89 MPa, H2 /oil ratio of 84.95 Sm 3 and LHSV of 1 hr -1 ) identified were also applied in the industrially relevant scale hydroprocessing pilot to validate the scale-up potential of the technology. The produced fuel is characterized by 5 wppm sulphur, 79.3 cetane index and 44.4 MJ/kg heating value, offering an advantage in compression ignition engines. The produced fuel can be blended up to 20% v/v with fossil diesel rendering a high bio-content diesel abiding by the EN 590 standard. It was found that, up to 20% per volume can be added in diesel without exceeding the requirements for CFPP standards for Greek winter diesel. Towards the commercialization of the technology with respect to the animal fats logistics, a dedicated 6-month storage stability study revealed that animal fats can be stored for up to three to four months at ambient conditions. The findings, indicate that the suggested technology is mature technology as applied successfully in the industrially-relevant-scale providing also the process data.